2019
DOI: 10.1186/s13104-018-3992-3
|View full text |Cite
|
Sign up to set email alerts
|

Early Implanon discontinuation rate and its associated factors in health institutions of Mekelle City, Tigray, Ethiopia 2016/17

Abstract: ObjectiveContraceptive discontinuation rate is very common in most developing countries, especially removal in the first year of use is common (18–63%), and the majority of these discontinuations are among women who are still in need of contraception. So the objective of this study was assessing early Implanon discontinuation rate and its associated factors in the study area. Institutional based cross sectional study was conducted and systematic random sampling technique was employed to interview the study par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 10 publications
13
32
2
Order By: Relevance
“…This might be due to its interference with their daily activities and unsatisfactory management. Even if most studies discussed about the overall counseling service given; this result is almost similar with different studies [ 5 , 9 , 17 , 19 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This might be due to its interference with their daily activities and unsatisfactory management. Even if most studies discussed about the overall counseling service given; this result is almost similar with different studies [ 5 , 9 , 17 , 19 ].…”
Section: Discussionsupporting
confidence: 85%
“…Early discontinuation of implanon is switching or stopping the method within 12 months of insertion and implanon discontinuation is defined as discontinuation at less than 2.5 years after insertion of implanon [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of early discontinuation of implants in this study is similar to that of a study done in Sudan which found a discontinuation rate of 43%. 21,22 However, the current proportion is higher than other studies conducted in Ethiopia, 16% 19 and 23.4%. 8 Other studies done in Ethiopia had a discontinuation rate higher than the current study.…”
Section: The Proportion Of Early Discontinuation Of Implantsmentioning
confidence: 77%
“…For instance, in a study conducted in Mekelle City, 34 percent of the women who were counselled discontinued early, while in the current study, 38.2 percent discontinued early of the women who were counselled. 22 In Uganda, a study that assessed early discontinuation of both contraceptive implants with an early discontinuation rate was 31% in the facility-based cross-sectional study conducted in the Wakiso District. This was lower compared to the current study, and the difference could be attributed to the denominator for assessing the proportion whereby the current study only included age of 18 years and above while the study done in Wakiso district included women of reproductive age 15-49 years from 42 health facilities in a rural and urban setting.…”
Section: The Proportion Of Early Discontinuation Of Implantsmentioning
confidence: 99%
“…The result was lower than studies in other developing countries. [21][22] This discrepancy might be due to sample size, timing of the study, socio-cultural differences, and the government's role in minimizing early removal of etonogestrel implant. The desire to become pregnant was the most common reason for early removal of implants in this study (32%), which infers that counseling services given to patients about the contraceptive method and its duration during inception is very essential.…”
Section: Discussionmentioning
confidence: 99%